Impact of biochar addition on three-dimensional structural changes in aggregates associated with humus during swine manure composting - Guo, Xiao-xia; Wu, Shu-biao; Wang, Xi-qing; Liu, Hong-tao (Journal of cleaner production, 2021)
Aerobic composting is widely used to recycle agricultural organic waste. From a micro perspective, the dynamic changes in the internal structure of compost aggregates during composting can reflect aeration conditions, which is worthy of further study to improve composting efficiency. This study set three composting treatments (swine manure: rice straw = 4:1 and 8:1, swine manure: rice straw: biochar = 8:1:1, wet mass ratio), to detect 3-D microstructures of compost aggregate with the involvement of humus and biochar during composting. The results showed that biochar addition to compost enhanced humic acid formation and humification degree, and it greatly decreased bulk density by 45.89% and increased free air space by 31.25% compared with the initial stage of the compost. Compost materials tended to become looser during composting, and biochar aided an increase in total porosity of compost aggregates by approximately 90% compared with other treatments, mainly attributed to decomposition effects. It is assumed that large aggregates break up with the assistance of biochar, and these small parts of the materials gradually stick together with the formation of humus colloids to develop final dense particles. Therefore, it can be concluded that when biochar is used as an additive, it can improve the physical structure with the involvement of humus during composting. [Display omitted] •Three-dimensional structures of compost aggregates were detected and analyzed.•Biochar aided an increase in total porosity of compost aggregates by about 90%.•Internal pores of compost aggregates became larger during composting.•Pore connectivity of aggregates was negatively related to humification degree.•Biochar caused breaking up effect, whereas humus colloids had cohesive effect.